1997
DOI: 10.1103/physrevb.56.1422
|View full text |Cite
|
Sign up to set email alerts
|

Localization and conductance fluctuations in the integer quantum Hall effect: Real-space renormalization-group approach

Abstract: We consider the network model of the integer quantum Hall effect transi-

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
72
2

Year Published

1998
1998
2008
2008

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(84 citation statements)
references
References 38 publications
10
72
2
Order By: Relevance
“…The actual initial distributions, P 0 (t), were chosen in such a way that corresponding conductance distributions, P 0 (G), were either uniform or parabolic, or identical to the FP distribution found semianalytically in Ref. 55. All these distributions are symmetric with respect to G = 0.5.…”
Section: Numerical Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The actual initial distributions, P 0 (t), were chosen in such a way that corresponding conductance distributions, P 0 (G), were either uniform or parabolic, or identical to the FP distribution found semianalytically in Ref. 55. All these distributions are symmetric with respect to G = 0.5.…”
Section: Numerical Resultsmentioning
confidence: 99%
“…55 Also, note that, in Refs. 70 and 72 the critical exponent ν was calculated using a procedure different from that described in Sec.…”
Section: Comparison With Previous Simulationsmentioning
confidence: 99%
See 1 more Smart Citation
“…An example in the case of V 0 < 0 is shown in Fig.1(a). In the absence of interband mixing, numerical calculations have suggested that there is still only one extended state in each LB while the value of the critical exponent ν is modified to be around 7/3 10 .…”
Section: The Semiclassical Model Including Inter-landau-band Mixingmentioning
confidence: 99%
“…The integrally quantized Hall plateaus (IQHP) are observed when the Fermi level lies in localized states, with the value of the Hall conductance, σ xy = ne 2 /h, related to the number of occupied extended states(n). Many previous studies 3,4,5,6,7,8,9,10,11,12,13,14,15,16,17,18,19,20,21,22,23 have been focused on so-called plateau transitions. The issue there is how the Hall conductance jumps from one quantized value to another when the Fermi level crosses an extended state.…”
Section: Introductionmentioning
confidence: 99%